2021
DOI: 10.1038/s41598-021-01643-2
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite exposure inhibits the erythroid differentiation of human hematopoietic progenitor CD34+ cells and causes decreased levels of hemoglobin

Abstract: Arsenic exposure poses numerous threats to human health. Our previous work in mice has shown that arsenic causes anemia by inhibiting erythropoiesis. However, the impacts of arsenic exposure on human erythropoiesis remain largely unclear. We report here that low-dose arsenic exposure inhibits the erythroid differentiation of human hematopoietic progenitor cells (HPCs). The impacts of arsenic (in the form of arsenite; As3+) on red blood cell (RBC) development was evaluated using a long-term culture of normal hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…The findings from our group have established that exposure to environmentally relevant levels of As III results in the development of anemia via the suppression of erythropoiesis in the bone marrow [14,[30][31][32][33][34]. In the present study, we found that the As3mt genotype has a critical role in mediating the hematotoxicity of arsenic.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The findings from our group have established that exposure to environmentally relevant levels of As III results in the development of anemia via the suppression of erythropoiesis in the bone marrow [14,[30][31][32][33][34]. In the present study, we found that the As3mt genotype has a critical role in mediating the hematotoxicity of arsenic.…”
Section: Discussionsupporting
confidence: 64%
“…However, the extent that As III directly mediates the suppression of erythropoiesis in vivo remains unknown. In the present study, we evaluated the contribution of the As3MT-dependent biotransformation to the arsenic-induced hematotoxicity identified in our previous experiments [14,[30][31][32][33][34]. This study provides novel information regarding the relative contribution of inorganic As III vs. methylated metabolites to the development of As III -induced anemia.…”
Section: Introductionmentioning
confidence: 94%